Faktor risiko kejadian multi drug resistant tuberculosis di RSUP Dr. Sardjito - Erma Nurjanah Widiastuti; Yanri Wijayanti Subronto; Dibyo Promono (Berita Kedokteran Masyarakat (BKM), 2017)
Determinant of multi-drug resistant tuberculosis events at Dr. Sardjito Hospital Yogyakarta PurposeThe purpose of this study was to identify the determinants of multidrug resistant events in patients with tuberculosis in Dr. Sardjito Hospital in Yogyakarta.MethodsA cross-sectional study was conducted involving 122 patients with suspected MDR TB consisting of 61 cases of MDR TB and 61 non MDR TB cases. The data collected were secondary data from MDR TB.06 registers, medical records, MDR TB.03 registers, and MDR TB patients' baseline data forms at Dr. Sardjito Hospital Yogyakarta from January 2012 until September 2016. Data were analyzed to determine the correlation between independent variables and dependent variable using Chi-Square tests, and to know the most dominant risk factors using multiple logistic regression tests.Results MDR TB patients’ characteristics showed there were more males (63.93%), age >45 years (52.46%), previously TB treatment (96.72%), never smoking (75.41%), no contacts with MDR TB patients (86.89%), and never examined for HIV-AIDS (59.02%). The analysis showed there was no significant association between age, sex, previous TB treatment, smoking, contact with MDR TB patients, and HIV-AIDS status with MDR TB incidence in Dr. Sardjito Hospital Yogyakarta (p value >0.05).Conclusion The variables of age, sex, previous TB treatment, smoking, contacts with MDR TB patients, and HIV-AIDS status were not risk factors for MDR TB incidence in Dr. Sardjito Hospital in Yogyakarta.